Impact Estimation Of Methane Hydrate Utilization On Atmospheric Carbon Emissions By Using Mass Balance Eco-Model - Tetsuo Yamazaki (International Marine Minerals Society, 2004)
Natural methane hydrate has been scientifically studied as a global carbon reservoir. However, in Japan, it?s potential as an energy resource has been industrially highlighted, because there are few domestic oil and natural gas resources in Japan, but many potential deposition areas for methane hydrate in the sea around Japan. Less CO2 discharge from methane compared with coal, oil and conventional natural gas for the same calorie value is considered an advantage for its use as an energy resource. Because methane hydrate is distributed at shallow depth in sediments on the ocean floor, accidental leakage of methane may occur while we utilize methane hydrate. Methane itself has a considerable impact on the greenhouse effect, if it reaches the atmosphere. Therefore, it is necessary to estimate its behavior in the environment after leakage if we want to use methane hydrate as energy resource. The mass balance after leakage of methane on the seafloor and in the water column can be studied through the analyses of natural cold seepages and hydrothermal activity.